The mediating role of psychological capital on the association between occupational stress and depressive symptoms among Chinese physicians: a cross-sectional study - Liu Li; Chang Ying; Fu Jialiang; Wang Jiana; Wang Lie (BMC, 2012)
Abstract Background Although occupational stress is an identified predictor of depressive symptoms, the mechanism behind the association is not well understood. The purpose of this study was to examine how psychological capital (PsyCap), a positive psychological state, mediates the association between occupational stress and depressive symptoms among Chinese physicians. Methods A cross-sectional survey was conducted in Liaoning Province, China, during September-October 2010. Self-administered questionnaires including items on depressive symptoms assessed by the Center for Epidemiologic Studies Depression Scale, occupational stress assessed by the effort-reward imbalance scale and PsyCap estimated by a 24-item Psychological Capital Questionnaire, together with age, gender, marital status and education were distributed to 1300 physicians employed in large general hospitals. The final sample consisted of 998 participants. Asymptotic and resampling strategies were used to examine how PsyCap mediates the association between occupational stress and depressive symptoms. Results Both the effort/reward ratio (ERR) and overcommitment were significantly associated with depressive symptoms among male and female physicians. There was a gender difference in the mediating role of PsyCap on the occupational stress-depressive symptoms association. For male physicians, PsyCap did not mediate the association between occupational stress and depressive symptoms. For female physicians, ERR and overcommitment were negatively associated with PsyCap, and PsyCap was negatively associated with depressive symptoms. As a result, PsyCap significantly mediated the associations of ERR and overcommitment with depressive symptoms. The proportion of PsyCap mediation was 19.07% for ERR, and 24.29% for overcommitment. Conclusions PsyCap could be a positive resource for combating depressive symptoms in Chinese physicians. In addition to reducing occupational stress, PsyCap development should be included in depression prevention and treatment strategies, especially for female physicians.